Modeling the Encephalopathy of Prematurity in Animals: The Important Role of Translational Research - Hannah C. Kinney; Joseph J. Volpe (Neurology Research International)
Translational research in preterm brain injury depends upon the delineation of the human neuropathology in order that animal models faithfully reiterate it, thereby ensuring direct relevance to the human condition. The major substrate of human preterm brain injury is the encephalopathy of prematurity that is characterized by gray and white matter lesions reflecting combined acquired insults, altered developmental trajectories, and reparative phenomena. Here we highlight the key features of human preterm brain development and the encephalopathy of prematurity that are critical for modeling in animals. The complete mimicry of the complex human neuropathology is difficult in animal models. Many models focus upon mechanisms related to a specific feature, for example, loss of premyelinating oligodendrocytes in the cerebral white matter. Nevertheless, animal models that simultaneously address oligodendrocyte, neuronal, and axonal injury carry the potential to decipher shared mechanisms and synergistic treatments to ameliorate the global consequences of the encephalopathy of prematurity.